A tourism development model : the case of Mexico - Aguilar, Cynthia Luna. ([s.n.], 2003)
The conditions of the national and international surroundings, which have favored the success of tourism in Mexico in the last fifty years, have radically changed. In this context, the analysis of the facotrs of change and definition of the new guidelines that must be followed in order to maintain Mexico as a world-class tourist country, become of a crucial importance.